2009
DOI: 10.1177/147323000903700215
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Differentiation of Human Placenta-derived Adherent Cells into Insulin-producing Cells

Abstract: This study investigated the differentiation of placenta-derived adherent cells (PDACs) into insulin-producing cells (IPCs). PDACswere cultured and the cells characterized by analysis of cell surface markers using flow cytometry. The PDACs were then treated with induction media containing basic fibroblast growth factor (bFGF) and bmercaptoethanol (b-ME). After induction, the presence of IPCs was demonstrated using dithizone staining, and the production of functional insulin was confirmed using immunocytochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 16 publications
(7 reference statements)
0
9
0
Order By: Relevance
“…It controls the maturation of pancreatic islet cells by regulating insulin 1 and other down stream genes. It was shown that the expression of PDX-1 is switched on first followed by other IPCs-related genes (41). Ngn3 appears transiently during the development of the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…It controls the maturation of pancreatic islet cells by regulating insulin 1 and other down stream genes. It was shown that the expression of PDX-1 is switched on first followed by other IPCs-related genes (41). Ngn3 appears transiently during the development of the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…PDX-1 controls the maturation of pancreatic islet cells by regulating insulin 1 and other downstream genes. It was shown that the expression of PDX-1 is switched on first followed by other IPCs-related genes [18]. In the current study, we have utilized Cnp in the one-step protocol, TSA in the two-step protocol, and β -mercaptoethanol in the three-step protocol to induce expression of PDX-1.…”
Section: Discussionmentioning
confidence: 99%
“…A very recent report [153] has suggested the differentiability of placenta-derived adherent cells into insulin-producing cells. The authors demonstrated for the first time that differentiated placenta-derived cells expressed Pdx-1, Insulin and Glut 2 genes.…”
Section: Placenta Derived Stem Cellsmentioning
confidence: 98%